Citrulline: A Multifunctional Compound for Health, Performance, and Therapeutic Applications - Mycyk, Marcin; Cioch, Michał Jakub; Kaczmarska, Urszula; Woźniak, Aleksandra; Nowak, Julia; Hermanowicz, Kamil; Doman, Katarzyna; Najdek, Agnieszka; Oleksy, Daria; Komada, Dawid (Journal of Education, Health and Sport, 2025)
Introduction: L-citrulline, a non-proteinogenic amino acid, is predominantly synthesized in the enterocytes of the small intestine, with smaller amounts produced in the kidneys, which plays a critical role in the detoxification of ammonia in the urea cycle, and serves as a precursor for nitric oxide (NO). Recent studies have highlighted citrulline's potential benefits in diverse physiological and pathological contexts, ranging from enhancing physical performance and muscle recovery to supporting cardiovascular health, mitigating endothelial dysfunction, and acting as a therapeutic agent in various health conditions. Aim of study: The study aims to provide a comprehensive summary of current knowledge on the biochemical characteristics, physiological functions, and therapeutic potential of citrulline. Materials and methods: A comprehensive scientific literature review was conducted using the PubMed database, focusing on studies published up to 2024, reporting experimental, clinical, or in vivo data related to citrulline's synthesis, biological functions, and therapeutic applications. Conclusion: Emerging evidence highlights citrulline's potential in treating various health conditions, such as erectile dysfunction, neurodegenerative diseases, and intestinal barrier dysfunction, as well as its protective effects in hepatic failure, wound healing, and oxidative stress-related damage. These findings suggest that citrulline may serve as a multifaceted therapeutic agent, meriting further research to optimize its clinical use.